Advancing Firm Growth Research: A Focus on Growth Mode Instead of Growth Rate - McKelvie, Alexander; Wiklund, Johan (Entrepreneurship Theory and Practice, 2010)
The development of firm growth research has been notably slow. In this paper, we argue that a major reason for this lack of development is the impatience of researchers to prematurely address the question of “how much?” before adequately providing answers to the question “how?” On the basis of an extensive review of the literature, we suggest how growth research can advance by changing focus to growth mode (organic, acquisition, hybrid). Toward this end, we provide a research agenda that helps establish the types of questions that growth researchers can ask within this new focus.